KORELASI ANTARA PELANGGARAN ATURAN WESTGARD TERHADAP NILAI SIX SIGMA PADA PENGENDALIAN KUALITAS PARAMETER PLATELET - Omry Adi; Moriska Ariyani Yulinar (LPPM Universitas Abdurrab, 2026)
Platelets are a hematological parameter with a high risk of reading error on hematology analyzer, necessitating stringent quality control to ensure the accuracy and precision of test results. Control evaluations are conducted using Levey-Jennings charts by applying Westgard rules and six sigma method to provide a comprehensive overview of the instrument’s accuracy and precision. This study aims to determine the correlation between Westgard rule violations and Six Sigma in the platelet quality control. The method used is a retrospective observational study using secondary data from internal quality control low, normal, and high levels results for the period January 1 – December 31, 2025, using hematology analyzer Sysmex XN-550. The result showed that the violations of the 10x rule were the most dominant (66,67%). Accumulative Spearman correlation test indicated a significant moderate positive correlation (p=0,391; p=0,018). At the high level, a strong correlation was obtained (r=0,649; p=0,022). Meanwhile, no significant correlations were found at the normal and low levels. Interpretation of six sigma values must be performed by considering the characteristics of each control level. Laboratories are recommended to implement sigma-based QC design by simplifying rules at high sigma to avoid false rejection and tightening rules (multirule) as well as control frequency at low sigma levels.